Approaches to Speaking: Challenges in Organizing Classroom Discussion and Possible Solutions - Akter, Aklima (Green University Review of Social Sciences, 2022)
This paper reviews a complete outline of different approaches to speaking, ways to initiate classroom discussion, problems in initiating classroom discussion and possible solutions. It also emphasizes on creating proper learning environment to teach speaking skills. This paper reviews various speaking activities and the problems that arise while initiating those activities in second language classroom. One of the goals of this paper is to provide teachers and educators to know more on various approaches to speaking. Another goal of this paper is to show various problems organizing classroom discussion and provide possible solutions to them. Green University Review of Social Sciences Dec 2021; 7(1-2): 155-164